Building response to long-distance major earthquakes - Pan, Tso Chien (2008)
Buildings in regions of low seismicity such as Singapore and Malaysia are usually designed without specific considerations for seismic loading. However, due to the far field effect of earthquakes in Sumatra, these buildings are occasionally subjected to tremors. From previous studies, it has shown that very large earthquakes (M>8.5) in Sumatra are frequent enough to be of engineering concern, which could cause low seismic excitations in Singapore. About 90% of the population in Singapore is housed in the high-rise public housing structures. This report therefore investigates the seismic vulnerability level of a typical high-rise public residential building in Singapore that does not consider seismic loads in its design.